2006
DOI: 10.1680/macr.2006.58.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Stress–strain behaviour of high-strength concrete columns confined by low-volumetric ratio rectangular ties

Abstract: Available test results and stress–strain models for poorly confined high-strength columns, more specifically for columns with a tie volumetric ratio smaller than 2·0%, are scarce. This paper presents test results loaded in the axial direction for square reinforced concrete (RC) columns confined by various volumetric ratio lateral ties including low volumetric ratio. Test variables include concrete compressive strength, tie yield strength, tie arrangement type and tie volumetric ratio. Local strains are measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…However, Polat (1992) and Razvi and Saatcioglu (1999) showed that lateral reinforcement with a yield stress of 1000 MPa reached its yield strength at the axial capacity of columns. Furthermore, previous investigations (Chung et al, 2002;Hong et al, 2006;Polat, 1992) …”
Section: Stress-strain Relationship Of Materialsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, Polat (1992) and Razvi and Saatcioglu (1999) showed that lateral reinforcement with a yield stress of 1000 MPa reached its yield strength at the axial capacity of columns. Furthermore, previous investigations (Chung et al, 2002;Hong et al, 2006;Polat, 1992) …”
Section: Stress-strain Relationship Of Materialsmentioning
confidence: 90%
“…As a result, many investigations (Bae and Bayrak, 2009;Chung et al, 2002;Hong et al, 2006;Hwang et al, 2005;Ozcebe and Saatcioglu, 1987;Sheikh and Khoury, 1993) have been conducted to try and enhance the lateral deformation capacity of reinforced concrete (RC) columns, which commonly demonstrate brittle failure under high axial loads or when made of high-strength concrete. From extensive experimental results (Bae and Bayrak, 2009;Hwang et al, 2005;Ozcebe and Saatcioglu, 1987;Priestley and Park, 1987;Sheikh and Khoury, 1993), the widely accepted perspective follows that the ductility capacity of RC columns can be improved by the confinement force provided by lateral reinforcements such as tie hoops or spiral bars.…”
Section: Introductionmentioning
confidence: 99%
“…It has been verified by theoretical analyses (Bai and Au, 2009;Kim et al, 2007;Lam et al, 2009;Pam and Ho, 2001) and experimental tests (Ahn and Shin, 2007;Bayrak and Sheikh, 1998;Ho and Pam, 2003a;2003b;Hong et al, 2006;Li et al, 1991;Sharma et al, 2007;Watson and Park, 1994;Xiao et al, 2008;Youssef and Rahman, 2007) that the flexural strength and ductility performance of reinforced concrete (RC) columns, including high-strength RC (HSRC) columns, can be improved significantly by installing a sufficient amount of transverse reinforcement to confine their concrete core. The transverse reinforcement not only averts brittle failure owing to shear, but also confines the core area to avoid premature concrete crushing and postpone inelastic buckling of longitudinal steel effectively.…”
Section: Introductionmentioning
confidence: 92%
“…Die Robustheit bzw. ausreichende Nachbruchtragfähigkeit wird in erster Linie durch die konstruktive Durchbildung der Querbewehrung gesteuert [2][3][4]. Der Einfluss von Bügeldurchmessern und Bügelabständen auf die Robustheit wurde bereits in [5,6] intensiv untersucht und die Ergebnisse in Form von erweiterten Konstruktionsregeln in [7] veröffentlicht.…”
Section: Introductionunclassified